Comparative analysis of traditional and modern methods in teaching English - Xandamova, Feruza (The Lingua Spectrum, 2025)
This article presents a comparative analysis of traditional and modern methods in teaching English. Traditional methods focus on grammar and writing skills, emphasizing the teacher’s role. Modern methods, on the other hand, aim to develop communicative skills, increase student engagement, and incorporate technology. The article analyzes the objectives, approaches, and significance of these methods in the learning process, examining their impact on the effectiveness of education.